Natural Mycoplasma bovis infection associated with epithelioid granulomatous caseonecrotic bronchiolitis at a progressed disease stage in calves - Suwanruengsri, Mathurot; Uemura, Ryoko; Uda Zahli, Izzati; Kanda, Takuya; Fuke, Naoyuki; Yasuda, Masahiro; Hirai, Takuya; Yamaguchi, Ryoji (Chulalongkorn University, 2022)
Mycoplasma bovis (M. bovis) is a pathogen that especially effects the respiratory system of cattle. We focused on the histopathological changes in the lungs caused by M. bovis because the lesions in the bronchi or bronchioles and alveoli are quite different in natural infections. Thirty-five lung samples from 2-to 12-month-old Japanese Black calves with respiratory symptoms were collected and examined for bacteria presence and pathological changes using immunohistochemistry (IHC). Using the loop-mediated isothermal amplification method, 18 of the 35 samples were found to be positive for M. bovis, which was isolated and identified. In 7 of the samples, only M. bovis was detected, whereas in the other 11, other bacteria coexisted with M. bovis. Anti-M. bovis, anti-MAC387, anti-Iba1, anti-CD3, anti-CD20, anti-AE1/AE3 cytokeratin and anti-IL8 were used for antigen detection. Histopathological studies and diagnoses of the lungs were examined in two parts; bronchiolar lesions and alveolar lesions. The bronchiolar findings were divided into three groups: granulomatous, caseonecrotic and suppurative bronchiolitis. The alveolar lesions found were quite mild, except in three cases. IHC staining revealed strong evidence of M. bovis in degenerated neutrophils, which was confirmed by electron microscopy. The main inflammatory cell response to M. bovis infections was degenerate neutrophils, which caused the destruction of the bronchial epithelium and possibly induced epithelioid granulomatous inflammation, resulting in severe chronic respiratory diseases in cattle.